Novel Parameters of Extended Complete Blood Cell Count under Fluorescence Flow Cytometry in Patients with Sepsis. Issue 2 (6th January 2014) - Arneth, Borros M.; Ragaller, Maximilian; Hommel, Kathleen; Tiebel, Oliver; Menschikowski, Mario; Siegert, Gabriele
<x xml:space="preserve">Abstract</x> Background We first describe a patient who developed urosepsis from an ordinary urinary tract infection. In this case, the new hematological parameters of immature leukocytes, that is, the high‐fluorescence lymphocyte cell (HFLC) and immature granulocyte (IG) counts peaked early, whereas the established infection parameters, that is, C‐reactive protein (CRP) and total white blood cell count showed less dynamic regarding infection and therapy. Methods To investigate this phenomenon in greater detail, the novel parameters HFLC and IG counts are investigated retrospectively in a cohort of 38 patients who were admitted to the anesthesia intensive care unit. Three groups of patients have been analyzed and compared: patients without signs of infection, patients with limited infections, and patients with sepsis. Data were collected with a Sysmex XE‐5000 hematological analyzer. Results In patients (n = 22) without any signs of infection, both values are very low. In patients with limited local infections (n = 10), moderate elevations of the IG and HFLC counts are seen. In patients with sepsis (n = 6), the IG and HFLC counts are significantly higher. Conclusion The total IG count seems to be useful for distinguishing a septic patient from a nonseptic (P < 0.004). Hematological parameters have the advantage of being measured easily during routine blood cell analysis.